Effects of smoking, gender and occupational exposure on the risk of severe pulmonary fibrosis: a population-based case-control study. Issue 1 (9th January 2014) - Ekström, Magnus; Gustafson, Torbjörn; Boman, Kurt; Nilsson, Kenneth; Tornling, Göran; Murgia, Nicola; Torén, Kjell
Abstract : Objectives: To estimate the effects of smoking, gender and occupational exposure on the risk of developing severe pulmonary fibrosis (PF), including dose-response and interaction effects. Methods: National case–control study of 171 patients (cases) who had started a long-term oxygen therapy for PF in Sweden between February 1997 and April 2000, and 719 random control participants from the general population. Of these cases, 137 had probable idiopathic PF (IPF). The ORs for smoking, gender and occupational exposure were estimated using Mantel-Haenszel analysis and conditional logistic regression, controlling for age and year of diagnosis. Results: The adverse effect of smoking was amplified by male gender and occupational exposure, OR 4.6 (95% CI 2.1 to 10.3) for PF, and OR 3.0 (1.3 to 6.5) for IPF, compared with in non-exposed women. Higher cumulative smoking exposure was linearly associated with increased risks. Compared with smoking less than 10 pack-years, smoking ≥20 pack-years was associated with increased risk of PF and IPF, OR 2.6 (1.4 to 4.9) and OR 2.5 (1.3 to 5.0), respectively. Conclusions: Smoking has a dose-related association with increased risk of severe PF. Men with a history of smoking and occupational exposure is a particular risk group for developing severe PF.